NORMS OF THE POPULATION’S HOSPITAL BED REQUIREMENT - GOLYACHENKO, O.M.; SHULGAY, A.H.; PANCHYSHYN, N.Y.; ROMANIUK, L.M.; SMIRNOVA, V.L.; TERENDA, N.O.; FEDCHYSHYN, N.Y.; PETRASHYK, Y.M. (Вісник соціальної гігієни та організації охорони здоров’я України, 2014)
Regular norms of provide hospital beds in Ukraine in 1.5-2 times exceed the foreign. Authors propose essentially new approach to reorganisation of hospital care by principle of treatment intensity. This will inevitably lead to qualitatively new changes on demand for beds and staff. KEY WORDS: norm, hospital bed, treatment intensity.